An empirical research on non-technical factors related to statistical data quality in China's enterprises. (19th July 2007) - Yu, Zhenguo; Wang, Ying
In market-oriented economy, data are the key factor that helps enterprises to make decisions. In China, many factors affect the data quality of enterprises. The paper chose seven non-technical factors as explanatory variables, three dimensions of data quality as dependent variables and one control variable to construct a conceptual model for Chinese enterprises. The model was tested with 152 samples. This research found that the main factors affecting the data quality are the awareness of higher-level managers, the status of statistical personnel, normalisation of enterprise, knowledge of statistical personnel, the strength of statistical department and enterprise computerisation.